2020
DOI: 10.1016/j.radcr.2020.08.061
|View full text |Cite
|
Sign up to set email alerts
|

Desmoid fibromatosis of the pancreas––A case report with radiologic-pathologic correlation

Abstract: Pancreas is an exceptionally rare location for desmoid tumors. There are very few case reports of pancreatic fibromatosis in the English radiology literature. We present a case of a 45-year-old male with a mixed solid and cystic desmoid tumor of the pancreas which was surgically resected and was followed by recurrence in the mesentery. This will be the first case report of pancreatic desmoid with documented recurrence of fibromatosis in the mesentery which was also surgically resected and confirmed on patholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…A DTF is a locally aggressive fibroblastic proliferation that is characterized by a variable and sometimes unpredictable clinical course [6] . In some instances, the lesions remain stable for long periods with no intervention, while in other cases, the lesions grow rapidly [7] .…”
Section: Discussionmentioning
confidence: 99%
“…A DTF is a locally aggressive fibroblastic proliferation that is characterized by a variable and sometimes unpredictable clinical course [6] . In some instances, the lesions remain stable for long periods with no intervention, while in other cases, the lesions grow rapidly [7] .…”
Section: Discussionmentioning
confidence: 99%
“…In solid pancreatic pseudopapillary tumor, weak early arterial enhancement and gradual increase in the portal-venous phase was characteristic manifestation[ 20 ]. Local invasion to adjacent vasculature causing pseudoaneurysms may also be observed in many pancreatic adenocarcinoma cases[ 21 ]. Our case is unique in that there werefew symptoms of the primary tumor, and paratesticular nodules werethe only first sign of metastasis and pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry is currently considered the most sensitive and specific method to determine the origin of the tumor. Singh et al [ 22 ] reported a case of duodenum bleeding due to metastatic endometrial adenocarcinoma which was confirmed by histology and positive cytokeratin 7, vimentin, and paired box gene 8 in immunohistochemistry[ 21 ]. In our case, mesothelioma was excluded due to thenegative expression of calretinin, MC, and WT-1.…”
Section: Discussionmentioning
confidence: 99%